RESOLUTE PET/MRI Attenuation Correction for O-(2-18F-fluoroethyl)-L-tyrosine (FET) in Brain Tumor Patients with Metal Implants - Ladefoged, Claes N.; Andersen, Flemming L.; Kjær, Andreas; Højgaard, Liselotte; Law, Ian (Frontiers in Neuroscience, 2017)
AIM: Positron emission tomography (PET) imaging is a useful tool for assisting in correct differentiation of tumor progression from reactive changes, and the radiolabeled amino acid analogue tracer O-(2-18F-fluoroethyl)-L-tyrosine (FET)-PET is amongst the most frequently used. The FET-PET images need to be quantitatively correct in order to be used clinically, which require accurate attenuation correction (AC) in PET/MRI. The aim of this study was to evaluate the use of the subject-specific MR-derived AC method RESOLUTE in post-operative brain tumor patients. METHODS: We analyzed 51 post-operative brain tumor patients (68 examinations, 200 MBq [18F]-FET) investigated in a PET/MRI scanner. MR-AC maps were acquired using: 1) the Dixon water fat separation sequence, 2) the ultra short echo time (UTE) sequences, 3) calculated using our new RESOLUTE methodology, and 4) a same day low-dose CT used as reference “gold standard”. For each subject and each AC method the tumor was delineated by isocontouring tracer uptake above a tumor(T)-to-brain background(B) activity ratio of 1.6. We measured B, tumor mean and maximal activity (TMEAN, TMAX), biological tumor volume (BTV), and calculated the clinical metrics TMEAN/B and TMAX/B. RESULTS: When using RESOLUTE 5/68 studies did not meet our predefined acceptance criteria of TMAX/B difference to CT-AC < +/-0.1 or 5%, TMEAN/B < +/-0.05 or 5%, and BTV < +/-2 mL or 10%. In total, 46/68 studies failed our acceptance criteria using Dixon, and 26/68 using UTE. The 95% limits of agreement for TMAX/B was for RESOLUTE (-3%;4%), Dixon (-9%;16%) and UTE (-7%;10%). The absolute error when measuring BTV was 0.7+/-1.9 mL (N.S) with RESOLUTE, 5.3+/-10 mL using Dixon, and 1.7+/-3.7 mL using UTE. RESOLUTE performed best in the identification of the location of peak activity and in brain tumor follow-up monitoring using clinical FET PET metrics. CONCLUSIONS: Overall, we found RESOLUTE to be the AC method that most robustly reproduced the CT-AC clinical metrics per se, during follow-up, and when interpreted into defined clinical use cut-off criteria and into the patient history. RESOLUTE is especially suitable for brain tumor patients, as these often present with distorted anatomy where other methods based on atlas/template information might fail.